CIVIL SOCIETY DAN KEHARMONISAN ANTARUMAT BERAGAMA: LARANGAN MUI PERIHAL PENGUCAPAN SALAM AGAMA LAIN DALAM KAJIAN LIVING HADIS - Elfada Adella Hidayat; Liliek Channa AW (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2021)
It is no longer surprising that Indonesia is still susceptible to finding many cases involving faith. Whether it is the entry of radicalism, which results in the rise of a derogatory stereotype toward Muslims in Christian circles, or even disputes among Muslims over who is the most right in his teachings. As stated in the Indonesian Ulama Council’s East Java Province declaration, which summarizes the findings of their tausiyah on greetings using other religious greetings. This assertion has sparked debate in a number of circles. Students, in particular, who work in a group or association that promotes interreligious harmony. Numerous them expressed reservations about the MUI comment. Given that students are considered to be a part of civil society, who would remain quiet if anything disturbs and impairs the community’s human rights? As such, this study seeks to ascertain the role of students as civil society in preserving religious believers’ unity in the face of disputes about how to express greetings from other religions and their relationship to the study of living hadith. Since the researcher explores historical events and takes a qualitative approach, this study is classified as historical research. After all, the researcher obtains data from carefully chosen informants. The findings of this study indicate that students of different religions are still attempting to preserve peace in a variety of ways, one of which is by not objecting to the greeting of other religions, as Islam contains a wealth of information about the sense of tolerance, both in the Qu’ran and the Hadith.